Assessing the validity of an instrumented medicine ball for measuring throw speed - Trunt, A.; Reed, C. A.; MacFadden, L. N. (Sports Engineering, 2023)
Medicine balls are a common training tool with important applications for sports performance, athletic development, and rehabilitation. However, the ability to quantify more descriptive throw outcomes such as speed and power using a medicine ball is challenging. Therefore, the purpose of this study was to assess the validity of the peak speed metric output from a medicine ball instrumented with an inertial measurement unit, across a range of ball masses, throw types, intensities, and conditions. One participant performed 156 throws recorded using optical motion capture as the reference system to collect 3D position data of the balls. Peak speed was calculated from this data and compared to the same metric reported from the instrumented medicine ball. A combination of Pearson`s correlation, linear models, and Bland-Altman analyses were used to determine if significant differences existed between devices, and to determine the between-device agreement and any sources of potential bias. No significant differences were found between measurement devices. Across all throws, a very strong relationship existed between devices for peak speed (r = 0.98). Significant, but small, bias was present between measurement devices for certain throw types, as the instrumented medicine ball either under-reported or over-reported peak speed by a mean value of - 0.17 to 0.2 m/s. While limitations of the instrumented medicine ball may exist at the ends of the device`s measurement range, its overall validity offers clinicians and coaches a tool to quantify medicine ball performance metrics for athletic development and rehabilitation purposes.